PENATALAKSANAAN FISIOTERAPI PADA KONDISI CALCANEUS SPURS BILATERAL DENGAN MODALITAS ULTRASOUND, TRANSVERSE FRICTION DAN HOLD RILEX EXERCISES DI RSUD BENDAN KOTA PEKALONGAN - Ayu Sulistiani Dianingtyas; Eko Budi Prasetyo (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2021)
Calcaneus Spur is an abnormal bone growth in the inferior part of the OS. Calcaneus, from the site of his special fibrokartilaginose cruciate ligament plantar facitis, which is a common cause of calcaneus Spur.problematicscalacaneus Spur is the presence of pain, spasm,weakness of muscle strength and the intracurate of functional acvity. In this case the selected technology is Ultrasound (US), transverse friction, and Rilex Hold. This research was conducted in The Hospital Of Bendan Pekalongan with the design of analytical descriptive research. The research subject is a patient with a bilateral calcaneus spur Condition with Ultrasound modalities (US), transverse Friction, and Rilex Hold. The research Instrument in the form of pain test, spasm, muscular strength and functional activity. The results of the study of 4 therapy as follows (1) There is a decrease in pain from T1 = 8 to T4 = 6 (2) There is no decrease in spasm of T1 = 1 remains t4 = 1 (3) The absence of increased muscle strength from t1 = 4 remains t4 = 4 (4) There is an increase in daily functional activities. The research conclusion brought physiotherapy intervention with Ultrasound modalities (US), transverse Friction, and Hold Rilex can reduce the problems caused in the bilateral calcaneus spurcondition.